2019
DOI: 10.1101/779835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LRRK2 is recruited to phagosomes and co-recruits Rab8 and Rab10 in human pluripotent stem cell-derived macrophages

Abstract: SummaryThe Parkinson’s disease-associated gene, LRRK2, is also associated with immune disorders and infectious disease, and is expressed in immune subsets. Here, we characterise a platform for interrogating the expression and function of endogenous LRRK2 in authentic human phagocytes, using human induced Pluripotent Stem Cell-derived macrophages and microglia. Endogenous LRRK2 is expressed and upregulated by interferon-γ in these cells, including a 18… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…However, in consideration of past reports, we acknowledge that other Rab proteins may eventually compensate for the loss of Rab10 with probable broader effects on endocytosis and vesicle traffic (Schuck et al, 2007). Several recently published reports have localized Rab10 recruitment to late endolysosomes (Eguchi et al, 2018;Lee et al, 2020). In contrast to these studies, we localized Rab10 recruitment on early macropinosomes loaded with soluble dextran in macrophage cells.…”
Section: Discussionmentioning
confidence: 75%
“…However, in consideration of past reports, we acknowledge that other Rab proteins may eventually compensate for the loss of Rab10 with probable broader effects on endocytosis and vesicle traffic (Schuck et al, 2007). Several recently published reports have localized Rab10 recruitment to late endolysosomes (Eguchi et al, 2018;Lee et al, 2020). In contrast to these studies, we localized Rab10 recruitment on early macropinosomes loaded with soluble dextran in macrophage cells.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, activation of TLR4 with LPS causes a redistribution of LRRK2 to membrane structures (Schapansky et al, 2014), and LRRK2 localizes to phagosome structures in monocytes infected with S. typhimurium (Gardet et al, 2010). LRRK2 is also required for co-recruitment of Rab proteins to late phagosomes in human IPS-derived macrophages exposed to different TLR2 and TLR4 activating pathogens (Lee et al, 2019). Further details of what occurs downstream of LRRK2 in TLR signaling remain to be elucidated, but phosphorylation of substrate Rab proteins is likely of interest given the published roles they may play in TLR biology (Wang et al, 2010;Luo et al, 2014).…”
Section: Lrrk2 and Toll-like Receptor Signalingmentioning
confidence: 99%
“…However, overexpression of LRRK2 has also been demonstrated to increase NFAT transcriptional activity in bone marrow derived dendritic cells (Takagawa et al, 2018), complicating the original interpretation of LRRK2 as a negative regulator of NFAT. Zymosan has also been shown to increase LRRK2 Ser910 andSer935 phosphorylation and LRRK2 localization Lee et al, 2019), although these effects are potentially mediated via TLR2 rather than dectin-1.…”
Section: Lrrk2 and C-type Lectin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…These derived microglial cells acquired a highly dynamic ramified morphology and exhibited neuronal surveillance activity mimicking the in vivo situation. Building on this advancement, a subsequent study demonstrated that LRRK2 expression in macrophages and microglia plays an important role in phagosome maturation and in the regulation of recycling pathways, implying that LRRK2 mutations in PD patients may disrupt microglial clearance mechanisms [ 131 ]. Additionally, it has been shown that the LRRK2-G2019S mutation influences fate decision in hiPSC-derived human monocytes, further endorsing the involvement of the immune system in the development of PD [ 132 ].…”
Section: Looking Into the Future: Optimization Of Hipsc-based Modementioning
confidence: 99%